Theory in the Pacific, the Pacific in theory : archaeological perspectives - Thomas, Tim, 1971- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
" 'Theory in the Pacific, the Pacific in Theory' explores the role of theory in Pacific archaeology, and its interplay with archaeological theory worldwide. The contributors assess how the practice of archaeology in Pacific contexts has led to particular types of theoretical enquiry and interest, and, more broadly, how the Pacific is conceptualised in the archaeological imagination. Long seen as a laboratory environment for the testing and refinement of social theory, the Pacific islands occupy a central place in global theoretical discourse. This volume highlights this role through an exploration of how Pacific models and exemplars have shaped, and continue to shape, approaches to the archaeological past. The authors evaluate key theoretical perspectives and explore current and future directions in Pacific archaeology. In doing so, attention is paid to the influence of Pacific people and environments in motivating and shaping theory-building. 'Theory in the Pacific, the Pacific in Theory' makes a significant contribution to our understanding of how theory develops attuned to the affordances and needs of specific contexts, and how those contexts promote reformulation and development of theory elsewhere. It will be fascinating to scholars and archaeologists interested in the Pacific region, as well as students of wider archaeological theory"--
OCLC-licensed vendor bibliographic record.
Keywords: Social archaeology -- Islands of the Pacific; Archaeology -- Islands of the Pacific -- Methodology; Archaeology -- Philosophy; Excavations (Archaeology) -- Islands of the Pacific; Islands of the Pacific -- Antiquities; SOCIAL SCIENCE / Archaeology